Between Adab And Digital Learning: A Qualitative Case Study In Indonesian Pesantren-Based Madrasah - Saifudin; Muchammad Aji; Irfan Musonif; Zaeni Gilang Darmawan; Aisyah Puan Maharani (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study examines how Islamic ethical values (adab) are negotiated within digital learning practices at a pesantren-based madrasah. While prior studies on digital Islamic education have predominantly focused on technological adoption and normative ethical integration, limited attention has been given to how adab is experienced and negotiated in everyday digital learning practices. This research aims to explore how these values are interpreted, adapted, and enacted by educational actors in situated contexts. Using a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis conducted between January and February 2026 at Madrasah Aliyah Roudlotut Tholibin, Banjarnegara, Indonesia. The findings reveal that adab is not diminished in digital contexts but transformed through situational negotiation involving students, teachers, and institutional authorities. This negotiation is reflected in digital communication practices, technology use, and shifting sources of knowledge. While institutional regulations seek to maintain ethical boundaries, students’ practical learning needs often lead to adaptive and context-dependent behaviors. Theoretically, this study reconceptualizes adab as a dynamic and negotiated social practice rather than a fixed normative construct. This contributes to the development of digital pedagogy in Islamic education by emphasizing the integration of ethical values within the fluid and participatory nature of digital learning environments.